Human Resources Development Strategy to Improve Service Quality at Ayu Siwi Eye Clinic Nganjuk - Anam, Moh Khoirul (Al-Hijrah Indonesia, 2025)
The quality of healthcare services in eye clinics is significantly influenced by effective human resource development (HRD), particularly in enhancing the competencies of medical personnel and administrative staff. However, challenges in implementing sustainable HRD strategies remain a common issue. This study aims to analyze HRD strategies in eye clinics and their impact on service quality. This research employs a qualitative descriptive design with a narrative approach. Data were collected through in-depth interviews with medical staff and clinic management, direct observations, and an analysis of HR-related policy documents. Participants in this study were drawn from Ayu Siwi Eye Clinic, located in Nganjuk, East Java. The sample included medical staff, administrative personnel, and managerial staff, all of whom had been employed at the clinic for at least one year. Thematic analysis was used to identify patterns in the strategies implemented. The findings indicate that effective HRD strategies include regular training, performance-based incentives, and employee involvement in decision-making processes. Clinics that adopt these approaches experience increased job satisfaction, operational efficiency, and improved patient care quality. However, challenges such as budget constraints and resistance to change among senior employees persist. In conclusion, the success of eye clinics in enhancing service quality relies on structured and sustainable HRD strategies. Innovative policies in HR management are essential to improving job satisfaction and service effectiveness.